Child abuse in ethnic regions: Evidence from 2899 girls in Southwest China. (October 2019) - Wan, Guowei; Wang, Miao; Chen, Sitao
Abstract: Objective: China has 55 ethnic minorities with 114 million population. As a piece of the worldwide picture of child abuse in ethnicity, the study on child abuse in Chinese ethnic regions is significant but insufficient currently. Therefore, this study examined the prevalence, negative effects, and risk factors of child abuse involving girls in Chinese ethnic regions. Method: A multi-stage cluster sampling procedure and paper-and-pencil questionnaire survey were used to conduct the study in 126 classes in three counties of Southwest China, which includes a total sample of 2899 girls. Results: The rates of physical abuse, emotional abuse, and neglect to girls in ethnic minority areas were significantly higher than those in the Han areas. Moreover, all types of child abuse negatively affected girls' mental health at different levels. However, the effects of abuse were more severe for girls in Han than for ethnic minorities with similar abuse severity. In addition, academic performance and parent-child relationship were correlated with child abuse for girls in the ethnic regions, and the risk was especially higher for girls in rural towns and those of younger age. Conclusion: Findings from this study indicated that the prevalence of child abuse of girls in ethnic regions was high. Although with lower prevalence of child abuse, girls in Han should be intervened for their more severe mental health problems with abuse than the peers in ethnic minority areas. Great attention should be paid to girls in ethnic regions with poor academic performance, bad parent-child relationship, especially in rural towns and in young age, to prevent the risk of child abuse.